Rapid Phenotypic and Metabolomic Domestication of Wild Penicillium Molds on Cheese - Ina Bodinaku (American Society for Microbiology, 2019)
ABSTRACT Fermented foods provide novel ecological opportunities for natural populations of microbes to evolve through successive recolonization of resource-rich substrates. Comparative genomic data have reconstructed the evolutionary histories of microbes adapted to food environments, but experimental studies directly demonstrating the process of domestication are lacking for most fermented food microbes. Here, we show that during adaptation to cheese, phenotypic and metabolomic traits of wild Penicillium molds rapidly change to produce domesticated phenotypes with properties similar to those of the industrial cultures used to make Camembert and other bloomy rind cheeses. Over a period of just a few weeks, populations of wild Penicillium strains serially passaged on cheese had reduced pigment, spore, and mycotoxin production. Domesticated strains also had a striking change in volatile metabolite production, shifting from production of earthy or musty volatile compounds (e.g., geosmin) to fatty and cheesy volatiles (e.g., 2-nonanone, 2-undecanone). RNA sequencing demonstrated a significant decrease in expression of 356 genes in domesticated strains, with an enrichment of many secondary metabolite production pathways in these downregulated genes. By manipulating the presence of neighboring microbial species and overall resource availability, we demonstrate that the limited competition and high nutrient availability of the cheese environment promote rapid trait evolution of Penicillium molds. IMPORTANCE Industrial cultures of filamentous fungi are used to add unique aesthetics and flavors to cheeses and other microbial foods. How these microbes adapted to live in food environments is generally unknown as most microbial domestication is unintentional. Our work demonstrates that wild molds closely related to the starter culture Penicillium camemberti can readily lose traits and quickly shift toward producing desirable aroma compounds. In addition to experimentally demonstrating a putative domestication pathway for P. camemberti, our work suggests that wild Penicillium isolates could be rapidly domesticated to produce new flavors and aesthetics in fermented foods.